Effects of Singapore's personal income tax reforms - Chio, Lin Ern (2008)
Over the years, many changes have been introduced to the Singapore’s personal income tax system. However, little research has been done to analyze the economic effects of these reforms. In this project, the effects of these reforms will be carefully analyzed and presented in seven main chapters.